PENINGKATAN KEMAMPUAN BERKOMUNIKASI LISAN DAN KECERDASAN EMOSIONAL DALAM KURIKULUM AKUNTANSI DITINJAU DARI PERSPEKTIF GENDER (Studi Empiris terhadap Mahasiswa Akuntansi UPN “Veteran” Jawa Timur) - Suryaningrum, Diah Hari (Journal of Accounting and Strategic Finance, 2009)
The objectives of this research are first, to prove that in the graduate education specially in accounting education, accounting curriculum is adequate in providing the students with other competences as well as cognitive skill. Second, to prove the influence of accounting education on emotional quotient (EQ) and the oral communication capability on the gender perspective. The special emphasis on the issue of gender in this study, with the consideration that there has been increasing recognition number of women accountant. Women role in the accounting history proved that in their household, women were responsible for the house financial. Thus, women have been practicing accounting and increasing their role within feminism as an accountant in their professional works and in education.This research employed new students and students who are finishing their accounting education. Hypotheses test used univariate and multivariate n-Way Anova. The results indicated, first, that there was no difference between women and men on the basis of their EQ and oral communication skill. It is proved that women are no less skilled than men, women have the same capability with men. Second, it indicated that there was a difference between new students’ EQ and oral communication skill and the finishing students. It is proved that curriculum of accounting education has significant impact on students’ skill. Key words: Gender, emotional quotient, oral communication skill.